ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR - Yohanes, Yohanes; Nariman, Augustpaosa (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study was conducted to determine the effect of independent commissioners, firm size, leverage, and profitability on earnings management. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018 – 2020. The sample was taken using the purposive sampling method and 162 samples were selected from 54 companies during the period 2018 – 2020. The study used a fixed effect regression model approach. Data processing using Eviews version 12. This study found that the independent board of commissioners had no significant effect on earnings management, firm size had a significant effect on earnings management, leverage had a significant effect on earnings management, and profitability had a significant effect on earnings management.